Origem, transporte e deposição do ouro em Manica (Moçambique) - d'Orey, F. L. C. (2010)
The different types of Archean gold deposits in the Manica greenstone belt of western Mozambique are briefely describcd in the context of their geological setting. Particular attention is devoted to the mineralogy, petrology, geological controls, refractoriness to treatment and prospection of these gold deposits. The genesis of gold was stratigraphically controled, but structural and metamorphic events related to the intrusion of late granites have concentrated and relocated the gold in different geological environments. The possibility of additional gold occurences in different rocks sequences is discussed as well as possible guidelines for future research and development.